Analisis Kandungan Zat Besi, Protein dan Mutu Organoleptik Cookies Substitusi Tepung Ikan Manyung dan Tepung Bayam Hijau sebagai Selingan Remaja Anemia - Wijrozun Nabila Fajriyati; Dian Ayu Ainun Nafies (Yayasan Literasi Sains Indonesia, 2024)
Anemia is a global health problem whose prevalence is still quite high. Iron deficiency anemia occurs due to a lack of iron in the blood or low levels of hemoglobin (Hb) in the body. The anemia threshold for adolescent girls is 12 g/dl, while for adolescent boys it is 13 g/dl. One way to increase iron intake in teenagers is to develop cookies that use substitutes for catfish flour and green spinach flour, which can be a healthy alternative snack. This research aims to analyze the effect of substitution of catfish flour and green spinach flour on the nutritional content of cookies. The research design used was a True Experimental Design with a Completely Randomized Design (CRD), which involved 4 treatments and 6 replications. The treatments applied included the ratio of wheat flour: catfish meal: green spinach flour at P0 (100:0:0), P1 (65:15:20), P2 (50:20:30), and P3 (30:25:45). The research results showed that the addition of green spinach flour could increase the macronutrient and iron content in cookies, with the highest iron levels found in the P3 treatment.